As crônicas de Nárnia, da literatura ao cinema: uma investigação intersemiótica - Brito, Talita Ferreira de Souza (2023)
This study aimed to investigate the intersemiotic relationships between C. S. Lewis's book The Chronicles of Narnia: The Lion, the Witch and the Wardrobe, first published in 1950, and the homonymous film released in 2005 and directed by Andrew Adamson. The Chronicles of Narnia comprise seven books that narrate the existence of a fantastic world. The Lion, the Witch and the Wardrobe, the first written and published chronicle, tells the story of how the four Pevensie siblings, the main characters, discovered this world inhabited by mythological creatures and talking animals. Despite being a work aimed at a children young people, some themes within the literary work prove to be complex for the aforementioned age group. Within this context, the objective of this study was to analyze how these same themes were reconstructed in the screen adaptation, identifying the strategies employed to make them suitable for the new format and audience, as well as analyze the results achieved by these choices. In addition to drawing from Translation Studies, particularly highlighting the work of Christiane Nord (2016), and Intersemiotic Translation, with emphasis on Júlio Plaza (2003), the research sought other paths of investigation by combining concepts from Semiotics and Adaptation Studies, in the light of authors such as Charles Sander Peirce (2005) and Deborah Cartmell (2012), respectively. Film language was another explored area, especially through the contributions of Bordwell and Thompson (2014), and, finally, the phenomena of intertextuality and hypertextuality were brought up through the definitions proposed by Gerárd Genette (2010).